Modified Training Circuit: an Effective Solution to Improve Handspring Skills in Floor Gymnastics - Muhammad Fitrah Mubarak; Irfan Deny Oktavian; Swandika Pinem; Ansar CS; Sifra Kafiar (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to analyze the effect of circuit training modification on improving handspring ability in floor gymnastics in students of the Jayapura City Special Sports School (SKO). The background of the study was based on the low mastery of handspring (only 30% of students were able to perform the technique correctly) which was indicated by weak arm push, hip flexibility, and balance. The method used was an experiment with a true experimental design, involving 30 students who were divided into experimental groups (provided with modified circuit training) and control (comparator). The intervention was given for 12 meetings, focusing on explosive arm muscle power training, hip flexibility, and balance. The results showed a significant increase in the experimental group (average 1.673) compared to the control (0.687), with a P value <0.05. These findings prove that circuit training modification is more effective in improving handspring ability because of its holistic and specific approach. This study recommends the integration of this method into the physical education curriculum to optimize floor gymnastics learning.